Implementasi Pembelajaran Berdiferensiasi Dalam Kurikulum Merdeka Belajar Pada Mata Pelajaran Pendidikan Agama Islam di SMP N 6 Lubuk Basung - Mia Audina; Fenny Ayu Monia; Mardiati M (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The diversity of student characteristics is one of the challenges for educators in implementing learning. The ability of educators to accommodate the diversity of characteristics and interests of students is the key to the success of the learning process itself. Differentiated learning is an adaptation effort in the classroom to meet students' learning needs. Therefore, we want to study further how Differentiated Learning is implemented in Islamic religious education learning, as well as the impact of Differentiated Learning on Islamic religious education learning for participants at SMP N 6 Lubuk Basung. This research is qualitative with a descriptive approach. Research data collection was obtained through interviews, observation and documentation. So the research instruments used consisted of interview guide sheets, observation guides, and documentation. The data obtained was analyzed using data analysis techniques consisting of Data reduction, Data Display, and conclusion drawing/Verification. This research will later produce results. Based on data measurement techniques, the research results will later show that The application of differentiated Islamic religious education learning. Â